Self-assembled adipose-derived mesenchymal stem cells as an extracellular matrix component- and growth factor-enriched filler - Park, Choa; Lee, Ok-Hee; Park, Jin Ju; Yoo, Jiyoon; Kwon, Euna; Park, Jie-Eun; Kang, Byeong-Cheol; Lee, Dong-Sup; Cho, Jaejin (Frontiers in Cell and Developmental Biology, 2023)
The clinical application of mesenchymal stem cells (MSCs) is attracting attention due to their excellent safety, convenient acquisition, multipotency, and trophic activity. The clinical effectiveness of transplanted MSCs is well-known in regenerative and immunomodulatory medicine, but there is a demand for their improved viability and regenerative function after transplantation. In this study, we isolated MSCs from adipose tissue from three human donors and generated uniformly sized MSC spheroids (~100 µm in diameter) called microblocks (MiBs) for dermal reconstitution. The viability and MSC marker expression of MSCs in MiBs were similar to those of monolayer MSCs. Compared with monolayer MSCs, MiBs produced more extracellular matrix (ECM) components, including type I collagen, fibronectin, and hyaluronic acid, and growth factors such as vascular endothelial growth factor and hepatocyte growth factor. Subcutaneously injected MiBs showed skin volume retaining capacity in mice. These results indicate that MiBs could be applied as regenerative medicine for skin conditions such as atrophic scar by having high ECM and bioactive factor expression.